DEVELOPMENT OF RECOMMENDATIONS IN INCREASE OF QUALITATIVE INDICES OF CASTINGS «SLEEVE» - V. A. Chajkin; A. V. Chajkin; A. N. Suhanov (Литьë и металлургия)
Recommendations on increase of qualitative indicators of castings «Sleeve» are given. It is shown that for modifying of melt it is offered to use just modifier MK95 in quantity of 4–6 kg per 1 ton of liquid metal.